Importance of the 2020 Croatia Earthquakes GIS-based Building Usability Database - Kadić, Alen (Crisis Management Days, 2024)
The 2020 Petrinja Earthquake caused many negative consequences, but also some positive effects on the future of the disaster risk reduction system in Croatia. One of them was to highlight the importance of the Croatian Centre for Earthquake Engineering and its elements, such as the 2020 Petrinja Earthquake GIS-based Building Usability Database. Initially, the database was used only by the Croatian Centre for Earthquake Engineering for internal use during Building Damage and Usability Assessment, as well as for reporting on the status of building damage in the area affected by the disaster, but gradually it proved to be a very valuable source of information for all stakeholders involved in the post-earthquake response and recovery. This led to the need for a more advanced database, which resulted in the creation of the 2020 Croatia Earthquakes Building Usability Database. This new comprehensive database enabled the continuous tracking of the real-time usability of buildings in the earthquake-affected area in correlation to the reconstruction process and other factors. Not only were the changes entered into the database daily, but the status of each building had to be checked daily as the numerous processes utilized the database as a relevant source of information. Three years after the 2020 Croatia Earthquakes, the importance of the database is still very high. Therefore, this database can serve as a case study for exploring the possible role of similar databases in the future that increase overall disaster resilience.